A Highland Christmas [large type] - Beaton, M. C. (Beaton, M. C. Hamish Macbeth mysteries., 2010)
A mystery without a murder featuring the series hero, Scottish constable Hamish MacBeth. The Christmas season brings him two cases, in one a woman reports her cat stolen, in another someone has stolen the village Christmas tree.